PERTANGGUNGJAWABAN PRODUSEN TERHADAP IKLAN YANG MERUGIKAN KONSUMEN - Anisa Elisawati; Azzhahro Geiza Salsabilla (JURNAL SUMBER HUKUM, 2025)
This discussion aims to examine the obligations of producers for misleading advertising from a managerial perspective with legal nuances. This discussion is descriptive qualitative from a literature review, namely by reviewing relevant literature, laws, and case studies to understand the phenomenon in depth and interpretatively. The results of the study indicate that producers should be held responsible not just policy assumptions but assumptions managerial ethics, consumer trust, and corporate social responsibility perspective. Thus, companies need to integrate responsible advertising strategies into their risk management and marketing governance. The legal frameworks, such as consumer protection laws, is also briefly discussed to illustrate how regulations intersect with company policies. This study contributes to the field of business ethics and consumer protection by offering an integrated perspective that aligns legal responsibility with ethical and managerial implications. Keywords: Accountability; advertising; trust; business ethics; consumer protection